RELATIONSHIP BETWEEN MOTIVATION WITH EDUCATION, TRAINING AND SKILL IN THE BUSINESS OF Swallow Cultivation AROUND THE SOUTH SULAWESI LAKE ‘’TEMPE’’ - AMIRUDDIN; NOR AZRIN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
The research entitled The Relationship Between Motivation and Education, Training and Skills in Swallow Cultivation Business Around Lake Tempe, South Sulawesi, aims to examine the relationship between business motivation and education, training and skills in swallow cultivation business. This research has been carried out for a year from February 2020 to January 2021 starting from the preliminary survey to data collection and analysis. This research was carried out in 3 (three) districts on the coast of Lake Tempe, namely Soppeng, Wajo and Sidrap Regencies, South Sulawesi Province. Data collection was carried out using purposive sampling (purposive sampling). taken as many as 327 respondents of swallow entrepreneurs from various levels of technology and varying length of business. Data collection was done by distributing questionnaires and interviews. Before the questionnaire was distributed, the instrument was tested, namely reliability and validity tests. The results showed that education, training and skills had a significant effect on the motivation to try swallow cultivation around Lake Tempe. Education, training and skills each had a partial effect on business motivation. Skill variables had a greater influence on business motivation. when compared to education and training.